Hypoxia‐inducible factor‐2α promotes hepatocyte apoptosis during cholestasis. Issue 1 (9th May 2016) - Hua, Xiangwei; Lu, Tianfei; Zhang, Jiang; Miao, Qi; Bian, Zhaolian; Zhang, Haiyan; Huang, Shanshan; Lin, Weiwei; Xi, Zhifeng; Zhang, Ming; Chen, Qimin; Ma, Xiong; et al.
Abstract : Aim : Hypoxia‐inducible factor‐2α (HIF‐2α) has been reported to play an important role in a host of pathophysiological processes, including cellular survival. This study explores the role of HIF‐2α in cholestasis‐mediated hepatocyte apoptosis. Methods : Hypoxia‐inducible factor‐2α expression was measured by immunohistochemistry and confocal microscopy. Hepatic apoptosis was detected by terminal deoxynucleotidyl transferase‐mediated dUTP‐digoxigenin nick‐end labeling. The cholestatic mouse model was treated with bile duct ligation. The c‐myc, p53, and Bax protein levels were measured with Western blot analysis. Results : In pediatric and murine cholestatic liver tissues, HIF‐2α protein was widely expressed in the nucleus of parenchymal cells as well as in stromal cells. Hepatocyte HIF‐2α expression was significantly elevated at the early stage of pediatric cholestasis and decreased at the late stage. In both in vivo and in vitro murine studies, HIF‐2α deletion could alleviate cholestasis‐mediated hepatocyte apoptosis and regulate the expression of c‐myc, p53, and Bax proteins. Conclusion : These findings implied the contribution of HIF‐2α to cholestasis‐mediated hepatocyte apoptosis.